Creating a Brand Identity: Case Arctic Orange - Leskinen, Wilma; Lindberg, Anita (Haaga-Helia ammattikorkeakoulu, 2019)
The goal of this thesis is to create a brand identity guideline, for the commissioner’s yet-to-be established startup called Arctic Orange, and it was done through creating and implementing our own brand identity creation model. As a product of the thesis, we created a brand identity that the commissioner could stand behind and that would reflect their values. We wanted to develop a product that the com-missioner could make use of when they create their company as well as in their future operations. Alongside this, our personal goal was to develop a business model and see, if the service we provided for Arctic Orange, could be turned into a real-life business. This thesis is commissioned by two well-experienced medical doctors, Mikko Aulu and Alpo Vuorio, who want to pass on their medical knowledge and create a service, where they help other companies market their products from a health and sustainability perspective. The theoretical framework of this thesis includes brand identity creation models from academic authors. However, due to lack of practical models available, we decided to implement and use our own model to build the brand identity. We wanted to include the customer in the creation process to ensure, that they are pleased with the outcome. This was one of the most important elements in our model. During the process, we consulted the commissioner several times to keep them updated on what has been done and what we are planning to do next. These checkpoints with the commissioner also gave structure to the process. Also, considering that Arctic Orange was not yet established as a business during this thesis process, our commissioner was very pleased to get to be involved in the brand identity creation. As a result of this thesis, we managed to create a professional and ready-to-use brand identity guideline for Arctic Orange, which they plan to take in use as it is.